## Example Problems on Estimators

ST702 Homework 4 on Estimators

# 7.6

Let $X_1, \dots X_n$, be a random sample from the pdf

$f(x | \theta) = \theta x^{-2} , \ 0 < \theta \leq x < \infty.$

## a

What is a sufficient statistic for $\theta$?

\begin{align} f( \mathbf x | \theta ) & = \prod \frac{ \theta }{ x_i ^2} I( 0 < \theta \leq x < \infty) \\ & = \frac{ \theta^n }{ \prod x_i^2 } I( \theta < x_{(1)}) \end{align}

By the factorization theorem, $X_{(1)}$ is sufficient.

## b

Find the MLE of $\theta$.

We calculated $L(\theta | x)$ above. Notice that it increases with $\theta$, so we want to maximize $\theta$. The max value it can take is $X_{(1)}$, so take $\theta = X_{(1)}$

## c

Find the method of moments estimator of $\theta$.

First we need to find $E(X)$.

$E(X) - \int_{\theta}^{\infty} x \frac{ \theta }{ x^2 } dx = \theta \log(x) |^{\infty}_{\theta} = \theta (\log(\infty) - \log(\theta)) = \infty$

Since $E(X)$ does not exist/ is not finite, the method of moments estimator does not exist.

# 7.11

Let $X_1, \dots , X_n$ be iid with pdf

$f(x | \theta) = \theta x^{\theta -1} , \ 0 \leq x \leq 1, \ 0 < \theta < \infty$

## a

Find the MLE of $\theta$, and show that its variance $\rightarrow 0$ and $n \rightarrow \infty$.

Notice that $f \sim Beta(\theta, 1)$.

\begin{align} L(\theta | x) & = \prod \theta X_i^{\theta - 1} \\ & = \theta^2 \prod\theta X_i^{\theta - 1} \\ \ell (\theta |x ) & = n \log(\theta) + (\theta -1 ) \sum \log(x_i) \\ \frac{ \partial \ell }{ \partial \theta }& = \frac{ n }{ \theta } + \sum \log(x_i) \\ & = 0 \\ \hat{\theta} & = \frac{ n }{ \sum - \log(x_i) } \\ \frac{ \partial^2 \ell }{ \partial \theta^2 } & = \frac{ - n^2 }{ \theta^2 } < 0 \end{align}

Notice that the second derivative is negative, meaning that this is indeed a maximum. Now we will use our knowledge of distribution relationships, so buckle up.

Our original function was a Beta distribution. We are taking the negative log of it, which is a $Exp(\frac{ 1 }{ \theta })$. We are then summing iid exponentials which gives a $Gamma(n, \frac{ 1 }{ \theta }$. Finally, we are taking the reciprocal of this, which is an inverse gamma. So, $\hat \theta \sim Inverse Gamma(n, \theta)$.

$V(\hat \theta) = V(n \cdot IG(n, \theta))= n^2 \frac{ \theta^2 }{ (n-1)^2(n-2) }$

Notice that the denominator grows in $n^3$ and the numerator in $n^2$, so the variance goes to 0 as $n \rightarrow \infty$.

## b

Find the method of moments estimator of $\theta$.

\begin{align} E(X) & = \frac{ \theta }{ \theta + 1 } \\ \frac{ 1 }{ n } \sum X_i & = \frac{ \theta }{ \theta + 1 } \\ - \theta \frac{ 1 }{ n } \sum X_i - \frac{ 1 }{ n } \sum X_i - \theta & = 0 \\ \theta(-\frac{ 1 }{ n } \sum x_i - 1) & = \frac{ 1 }{ n } \sum X_i \\ \hat \theta & = \frac{ 1/n \sum X_i }{ -\frac{ 1 }{ x } \sum X_i - 1 } \end{align}

# 1

Suppose that a random variable $X$ has Poisson distribution for which the parameter $\lambda > 0$ is unknown. Find a statistic $\tau(X)$ that will be unbiased for $e^\lambda$. Hint: If $E\Big[ \tau(X) \Big] = e^\lambda$, then $\sum_{x=0}^{\infty} \frac{ \tau(x) e^{-\lambda} \lambda^x }{ x! } = e^\lambda$. Multiply both sides of this equation by $e^\lambda$; expand the right hand side in a power series of $\lambda$, and then equate the coefficients of $\lambda^x$ on both sides of the equation for $x=0, 1, \dots$.

\begin{align} \sum_{x=0}^{\infty} \frac{ \tau(x) e^{-\lambda} \lambda^x }{ x! } & = e^\lambda \\ e^\lambda \sum_{x=0}^{\infty} \frac{ \tau(x) e^{-\lambda} \lambda^x }{ x! } & = e^\lambda e^\lambda \\ \sum_{x=0}^{\infty} \frac{ \tau(x) \lambda^x }{ x! } & = e^{2 \lambda} \\ & = \frac{ (2 \lambda)^0 }{ 0! } + \frac{ (2 \lambda)^1 }{ 1! } + \frac{ (2 \lambda)^2 }{ 2! } + \frac{ (2 \lambda)^3 }{ 3! } + \dots \\ & = 1 + \frac{ 2 \lambda }{ 1! } + \frac{ 2^2 \lambda^2 }{ 2! } + \frac{ 2^3 \lambda^3 }{ 3! } + \dots \end{align}

So take $\tau(X) = 2^X$.

# 2

Let $X_1, X_2, \dots X_n$ be a random sample from a distribution whose first two moments are finite. Let $\mu = E(X)$ and $\sigma^2 = V(X)$. Determine an unbiased estimator for $\mu^2$.

Take $\tau(X) = \frac{ 1 }{ n } \sum_{i=1}^{n}(X_i^2) - S^2$. Then,

\begin{align} E\Big[ \frac{ 1 }{ n } \sum_{i=1}^{n}(X_i^2) - S^2 \Big] & = E\Big[ \frac{ 1 }{ n } \sum_{i=1}^{n}(X_i^2) \Big] - E(S^2) \\ & = \frac{ 1 }{ n } E\Big[ \sum_{i=1}^{n}(X_i^2) \Big] - \sigma^2 \\ & = \frac{ 1 }{ n } \sum_{i=1}^{n}\Big[ E(X_i^2) \Big] - \sigma^2 \\ & = \frac{ 1 }{ n } \sum_{i=1}^{n} \Big[ E(X_i^2) \Big] - \sigma^2 \\ & = \frac{ 1 }{ n } \sum_{i=1}^{n} \Big[ E(X_i)^2 + V(X_i) \Big] - \sigma^2 \\ & = \frac{ 1 }{ n } \Big[ n \mu^2 + n \sigma^2 \Big] - \sigma^2 \\ & = \mu^2. \end{align}